2018
DOI: 10.1111/jdv.14910
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported symptoms and signs of moderate‐to‐severe psoriasis treated with guselkumab or adalimumab: results from the randomized VOYAGE 1 trial

Abstract: BackgroundHow patients experience the symptoms/signs of psoriasis is highly relevant for assessing treatment response.ObjectivesCompare outcomes with guselkumab, placebo and adalimumab utilizing the novel, validated Psoriasis Symptoms and Signs Diary (PSSD).Methods VOYAGE 1 is an ongoing, phase III, double‐blinded, controlled trial of patients with moderate‐to‐severe psoriasis. Patients were randomized to guselkumab 100 mg every 8 weeks; placebo‐to‐guselkumab 100 mg every 8 weeks; or adalimumab 40 mg every 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Pruritus-reducing effects of biologic treatment on psoriatic pruritus have been reported (393)(394)(395)(396)(397)(398)(399)(400)(401). One single report of cases referred to persistent CP (402).…”
Section: 411mentioning
confidence: 99%
“…Pruritus-reducing effects of biologic treatment on psoriatic pruritus have been reported (393)(394)(395)(396)(397)(398)(399)(400)(401). One single report of cases referred to persistent CP (402).…”
Section: 411mentioning
confidence: 99%
“…Nevertheless, UVB phototherapy and cyclosporine were also noted to be effective. Some studies showed the favorable effects of ustekinumab (anti-IL12) (37) and anti-IL23 (38) on pruritus. A topical inhibitor of nerve growth factor (NGF) receptor has also been shown to be effective for the treatment of pruritus due to psoriasis (39).…”
Section: Psoriasis Vulgarismentioning
confidence: 99%
“…The efficacy and safety of guselkumab treatment for psoriasis was demonstrated in three phase III trials (VOYAGE 1, VOYAGE 2, NAVIGATE) [ 126 128 ]. Furthermore, Papp et al [ 129 ] revealed that patients receiving guselkumab ( n = 249) experienced higher improvement of itch severity (assessed using the Psoriasis Symptoms and Signs Diary) than in the placebo ( n = 129) and adalimumab ( n = 274) groups ( p < 0.001).…”
Section: Biologic Drugsmentioning
confidence: 99%